Incidence trends and age-period-cohort analysis of Alzheimer’s disease and other dementias in the world and China from 1990 to 2021: analyses based on the Global Burden of Disease Study 2021 - Zhang, Xuewang; Lu, Hanxin; Xiong, Jun (Frontiers in Neurology, 2025)
BackgroundWith the accelerating global population aging, the incidence rates of Alzheimer’s disease and other dementias (ADOD) continue to rise sharply, presenting a pressing public health challenge worldwide. In China, where population aging is occurring at an unprecedented rate, the epidemiological trajectory of ADOD has garnered significant attention. The marked increase in incidence rates has imposed a substantial burden on both society and families, driven by direct healthcare costs, long-term care demands, and productivity losses among caregivers.MethodsThis study utilized the age-period-cohort model to analyze the changes in the incidence and disability-adjusted life years (DALYs) rate of ADOD among the elderly population in China from 1990 to 2021, considering the dimensions of age, period, and cohort. The necessary data for this analysis were sourced from the Global Burden of Disease (GBD) 2021.ResultsFrom 1990 to 2021, the incidence, prevalence, and DALYs of ADOD have significantly risen both globally and in China, with the growth rates in China notably surpassing the global average. China’s age-standardized incidence rate demonstrated an annual percent change of 0.921 (95% UI: 0.817, 1.025), with females (1.107) exhibiting a higher trend compared to males (0.695). The Average Annual Percentage Change (AAPC) for prevalence reached 5.995 (95% UI: 5.327, 6.664), significantly exceeding the global figure of 0.617. Age-effect analysis indicated that the effect coefficient for the 60–64 age group was 197.30, escalating dramatically to 3698.13 for the 85–89 age group, thus highlighting an exponential increase in risk with advancing age. The period effect peaked at 1.04 during 2018–2021, which is associated with accelerated aging and improvements in diagnostic techniques. In cohort analysis, the risk for individuals born between 1950 and 1954 increased compared to those born between 1895 and 1899.ConclusionChina is confronted with a dual challenge: the escalating burden of ADOD and a rapidly aging population, with female populations disproportionately affected. Urgent, gender-sensitive interventions are essential to enhance early detection, improve long-term care, and address modifiable risk factors. This study emphasizes the necessity for sustained investments in public health infrastructure and research to mitigate the increasing societal and economic impacts of ADOD.